Quantifiable effects of regular exercise on zinc status in a healthy population-A systematic review. - Anna Chu; Trishala Varma; Peter Petocz; Samir Samman (PLoS ONE)
Zinc is an essential mineral of which its functions have potential implications on exercise performance and beneficial adaptations of physical activity. While the effects of aerobic exercise on zinc metabolism acutely have been well described, the effect of long-term exercise training on zinc status remains unclear. The present review aims to determine the effects of exercise training on markers of zinc status in an apparently healthy adult population. We conducted a systematic literature search on PubMed, Scopus, SPORTDiscus and Cochrane Library from inception to 28 January 2016 to identify interventional or cohort studies that investigated the effects of exercise training on indices of zinc status. Pairwise comparisons of mean differences in within-group change were calculated and summarised visually in forest plots. Six studies satisfied the inclusion criteria for the systematic review, of which 5 studies included data on changes in serum zinc concentrations and 3 studies provided changes in dietary zinc intake. Two comparisons showed significantly higher increase of serum zinc concentrations in the exercise group compared to control, while one comparison reported significantly lower change in serum zinc for the exercising group. The exercise groups consumed significantly higher dietary zinc compared to controls in two comparisons. The present review revealed an incomplete evidence base in evaluating the effect of long-term exercise training on markers of zinc status. Further well-designed investigations are required to elucidate the relationship for establishment of dietary recommendation in populations who are continuing exercise interventions.